Pan African feminist perspectives on women’s labour contribution and economic participation in Kenya’s export horticulture production - Ngutu, M.; Bukachi, S.; Onyango-Ouma, W.; Liani, M.L. (2026)
This article applies the social relations approach (SRA) and the feminist political economy theory to critically analyze the complex realities of women’s work in export horticulture as shaped by intersectional inequalities and labour rights violations in both productive and reproductive spheres. We interrogate in-depth the experiences of women in their horticulture wage work, as in the ethnographic qualitative research conducted in Northwest Mount Kenya’s export horticulture sector. The findings detail how women navigate the triple gender role in pursuit of decent work. This critical lens moves beyond conventional analysis of women’s labour contribution in export horticulture to address the intersecting oppressions of gender, class, and other social factors, centred on women’s lived experiences, histories, and knowledge systems to challenge the social reproduction of inequalities. We argue for transformative interventions for women working in export horticulture to address the intersectional inequalities that shadow their labour contribution in agriculture and limit their access to benefits for sustainable livelihoods.